Audit Quality, Earnings Management, and Cost of Equity Capital: Evidence from India. Issue 2 (29th January 2017) - Houqe, Muhammad Nurul; Ahmed, Kamran; van Zijl, Tony
Abstract : This study examines the effect of audit quality on earnings management and cost of equity capital of listed companies in India. Our results show that companies employing a high‐quality auditor have a lower degree of earnings management and lower cost of equity capital. The results also show that companies belonging to business groups have a lower degree of earnings management and lower cost of equity capital than do stand‐alone companies but that they benefit less from employing a high‐quality auditor. Our results are based on a large sample of 7, 303 firm‐year observations on listed companies in India and are robust to alternative measures for our main variables – audit quality, earnings management, and cost of capital – and to tests for endogeneity and the impact of the global financial crisis (GFC). Given the distinctive and unique institutional features of the Indian market such as the dominant role of family business groups in the national economy, large market share of domestic audit firms, less litigious environment, and less effective professional accounting bodies in checking audit failure, our findings make a significant contribution to the literature on the role of audit quality as a corporate governance monitoring mechanism as reflected in the impact on earnings management and cost of equity capital.